Piano di uguaglianza di genere dell'Università degli Studi di Cagliari (UNICApress, 2023)
Through the adoption of the Gender Equality Plan, the University of Cagliari proposes itself as a strategic agent for the promotion of the European founding principle of gender equality, in its dual capacity as a place of socialization aimed at combating inequalities and applying the equity principles of substantive citizenship, and as a work organization characterized by diversities that can translate into the risk of inequalities in the distribution of positions and progression along professional paths.